Development and psychometric properties of the critical thinking attitude scale in Italian college students - Fabio, Rosa Angela; Antonietti, Alessandro; Iannello, Paola; Suriano, Rossella (Frontiers in Psychology, 2025)
IntroductionCritical thinking (CT) is a higher-order cognitive skill essential for academic and professional success, combining the ability to evaluate evidence with a reflective and analytical attitude toward information. Although several tools exist to measure critical thinking disposition, many show limitations in length, reliability, or generalizability, often focusing on specific populations such as medical and nursing students. This study addresses this gap by developing and validating the Critical Thinking Attitude Scale (CTAS) for Italian university students.MethodsThe study was conducted in two phases. In Study 1, 211 participants completed the CTAS questionnaire; exploratory factor analysis revealed a four-factor structure: systematicity, search for truth and openness, analyticity, and inquisitiveness, with high internal consistency (α > 0.78). In Study 2, involving 577 participants, the four-factor model was confirmed through confirmatory factor analysis, showing excellent reliability (α = 0.93) and significant correlations with the Critical Reasoning Assessment (CRA) and the Italian Big Five Inventory (BFI-10), supporting convergent validity, while negative correlations with the Dysfunctional Beliefs Questionnaire (DBQ) highlighted divergent validity.ResultsExploratory and confirmatory analyses supported a robust four-factor structure of the CTAS, demonstrating excellent internal consistency and reliability. Convergent validity was confirmed through positive correlations with CRA and BFI-10, whereas divergent validity was supported by negative correlations with DBQ.DiscussionThis study fills an instrument gap by providing the first Italian adaptation of the CTAS, offering a psychometrically robust and culturally appropriate tool for assessing attitudes toward critical thinking across disciplines. The findings provide a foundation for targeted educational interventions and future research aimed at fostering reflective and analytical thinking in higher education, contributing a standardized, valid, and broadly applicable measure.